Dissecting the 17β‐estradiol pathways necessary for neuroglobin anti‐apoptotic activity in breast cancer. Issue 7 (19th January 2018) - Fiocchetti, Marco; Cipolletti, Manuela; Ascenzi, Paolo; Marino, Maria
Abstract : Neuroglobin (NGB) is a relatively recent discovered monomeric heme‐protein, which behave in neurons as a sensor of injuring stimuli including oxidative stress, hypoxia, and neurotoxicity. In addition, the anti‐apoptotic activity of overexpressed NGB has been reported both in neurons and in cancer cell lines. We recently demonstrated that, NGB functions as a compensatory protein of the steroid hormone 17β‐estradiol (E2) protecting cancer cells against the apoptotic death induced by oxidative stress. However, the E2‐induced signaling pathways at the root of NGB over‐expression and mitochondrial re‐localization in breast cancer cells is still elusive. By using a kinase screening library, here, we report that: i) There is a strong positive correlation between NGB and ERα expression and activity in breast cancer cells; ii) The E2‐activated phosphatidyl‐inositol 3 kinase (PI3K)/protein kinase B (AKT) and protein kinase C (PKC) pathways are necessary to modulate the NGB protein levels; iii) The E2‐induced persistent activation of AKT drive NGB to mitochondria; iv) Reactive oxygen species (ROS)‐inducing compounds activating rapidly and transiently AKT does not affect the NGB mitochondrial level; and v) High level of NGB into mitochondria are necessary for the pro‐survival and anti‐apoptotic effect of this globin in cancer cells. As a whole, these results underline the E2 triggered pathways in E2‐responsive breast cancer cells that involve NGB as a compensatory protein devoted to cancer cell survival. Abstract : Neuroglobin is a conserved compensatory protein induced by 17β‐estradiol to increase breast cancer cell survival. The estrogen receptor alpha subtype‐activated PI3K/AKT signaling is the main intracellular upstream pathway by which estradiol affects neuroglobin function. This new pathway could open a treasure trove for development and pre‐clinical evaluation of novel therapeutics for the treatment of breast cancers.